EFEKTIVITAS PROGRAM MENTORING TERHADAP PENINGKATAN PENGETAHUAN KESELAMATAN PASIEN - Andalia Roza Andalia Roza; Putri Wulandini (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
Patient safety culture is fundamental in implementing safety in a hospital. Hospitals must ensure the application of patient safety in the health services they provide to patients. The foundation of good patient safety will improve the quality of health services, especially nursing care. Efforts to implement a patient safety culture can be various and mentoring is a more appropriate way. This is because mentoring can provide support to individuals in the learning process with more strength. This research uses quasy experimental research with a non equivalent design. This design consists of two groups, namely the experimental group and the control group. Then the pre-test was done in both groups, and intervention was followed in the experimental group. After four mentoring sessions, a new post test was carried out on both groups. The research was conducted D III Nursing Abdurrab University, Pekanbaru. The research sample in this study is nursing students who will practice nursing clinics. The sampling technique used is random sampling. The research instrument used for this research was a pre-test and post-test questionnaire about patient safety knowledge along with a mentoring program to increase patient safety knowledge. data processing includes editing, coding, processing, cleaning, and tabulating. Data analysis included: validity & reliability test, univariate analysis and bivariate analysis using SPSS assistance. The results of the study were obtained There was a change in knowledge in the experimental group with a p-value of 0,000; there was a change in knowledge in the control group and the experimental group in the post test with a p value of 0.00. It is expected that educational institutions will find out how students are prepared to enter the hospital about Patient Safety. Keyword : Patient Safety, Mentoring